Analisis Tingkat Kepuasan Konsumen Terhadap Pelayanan Ojek Online (Grab) Di Kota Parepare - Kurniawan Kurniawan; Andi Sulfanita; Hendro Widarto; Adnan Adnan (Departement of Mathematics Education, 2024)
The increasing demand for transportation services has made various transportation service entrepreneurs take various ways to improve their services, including creating online transportation services called online motorcycle taxis. The quality of service to consumers is very determining in measuring the level of customer satisfaction because these things are closely related to each other. This research aims to determine the level of consumer satisfaction with online motorcycle taxi services named Grab based on 5 dimensions of service quality. The method used in this research is quantitative descriptive and is analyzed using the Statistical Package For Social Sciences or SPSS program version 24. The research results show that the customer response to the 5 dimensions of service quality which are tangible, empathy, responsiveness, reliability and assurance is 77.8%. This is means the customer are happy to use online motorcycle taxi transportation service from Grab because this value is in the good category.